The Population Dynamics of Belanger's Croaker (Johnius belangerii) at Barumun River, Panai Hilir District, Labuhanbatu Regency - Maryani, Sri; Machrizal, Rusdi (Biosfer: Jurnal Tadris Biologi, 2022)
This study aims to determine the population dynamics of J. belangerii fish in the waters of the Barumun River, Labuhanbatu Regency. Sampling was carried out for 3 months, starting in October – December 2021. The results showed the relationship between length and weight of J. belangerii fish was negative allometric with a b value of 0.713 (b<3). The population of J. belangerii was dominated by individual lengths between 14.5 - 38 cm with a body weight range of 30-80 grams. The length of the totic acid (L∞) is 41.55 cm with a growth coefficient (K) of 0.430 per year. Natural mortality (M) and fishing mortality (F) were 0.937 and 0.892 per year, respectively. The level of exploitation (E) obtained a value of 0.35 . The condition of the population of J. belangerii based on the value of (F),(N),(E) is not in a state of over-exploitation.ABSTRAK: Penelitian ini bertujuan untuk mengetahui dinamika populasi ikan J. belangerii yang ada di Perairan Sungai Barumun Kabupaten Labuhanbatu. Pengambilan sampel dilakukan selama 3 bulan, di mulai pada Oktober – Desember 2021. Hasil penelitian menunjukkan hubungan Panjang berat ikan J. belangerii adalah alometrik negatif dengan nilai b 0,713 (b<3). Populasi ikan J. belangerii didominasi ukuran panjang individu antara 14,5 - 38 cm dengan kisaran berat tubuh 30-80 gram. Panjang asim totik (L∞) adalah 41,55 cm dengan koefisien pertumbuhan (K) adalah 0,430 pertahun. Mortalitas alami (M) dan mortalitas penangkapan (F) masing-masing sebesar 0,937 dan 0,892 per tahun. Tingkat eksploitasi (E) diperoleh nilai 0,35 . Kondisi populasi J. belangerii berdasarkan nilai (F),(N),(E) tidak dalam keadaan over exploitasi.